OXIDATIVE STRESS AND REPRODUCTIVE FUNCTION: Oxidative stress in polycystic ovary syndrome. Issue 6 (22nd November 2022) - Rudnicka, Ewa; Duszewska, Anna Maria; Kucharski, Marek; Tyczyński, Paweł; Smolarczyk, Roman
Abstract : In brief: A genetic, epigenetic, and environmental association exists between oxidative stress (OS) and polycystic ovary syndrome (PCOS), expressed in a multifaceted clinical profile. This review summarizes and discusses the role of OS in the pathogenesis of PCOS syndrome, focusing on metabolic, reproductive, and cancer complications. Abstract: Oxidative stress (OS), an imbalance between oxidants and antioxidants in cells, is one of many factors playing essential roles in the pathogenesis of polycystic ovary syndrome (PCOS). PCOS is described mainly as a disproportion of reproductive hormones, leading to chronic anovulation and infertility in women. Interestingly, OS in PCOS may be associated with many disorders and diseases. This review focuses on characteristic markers of OS in PCOS and the relationship between OS and PCOS related to insulin resistance (IR), hyperandrogenemia, obesity, chronic inflammation, cardiovascular diseases, and cancer. Interestingly, in patients with PCOS, an increase in oxidative status and insufficient compensation of the increase in antioxidant status before any cardiovascular complications are observed. Moreover, free radicals promote carcinogenesis in PCOS patients. However, despite these data, it has not been established whether oxygen stress influences PCOS development or a secondary disorder resulting from hyperglycemia, IR, and cardiovascular and cancer complications in women.